2020
DOI: 10.1029/2020ja028573
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing the Time‐Dependent Nature of Magnetosphere‐Ionosphere Coupling via ULF Waves at Substorm Onset

Abstract: Azimuthal structuring is usually observed within the brightening auroral substorm onset arc; such structure has been linked to the exponential growth of electromagnetic ultralow-frequency (ULF) waves. We present a case study investigating the timing and frequency dependence of such ULF waves on the ground and in the near-Earth magnetotail. In the magnetotail, we observe an increase in broadband wave power across the 10-to 100-s period range. On the ground, the arrival times spread from an epicenter. The onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 96 publications
(192 reference statements)
0
12
0
Order By: Relevance
“…This interval time is associated with Alfvén transit time from the substorm onset region to the footprint ionosphere (e.g., Liou et al, 2002). Smith et al (2020) reported that the travel time from the spacecraft to the ground is about 1−2 min for ULF waves in the near-Earth magnetotail. But outside the substorm onset region, the beginning magnetic elevation is smaller than that within the substorm onset region shown in Figure 4g, θ ~ 45°a nd Figure 5g, θ ~ 30°, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This interval time is associated with Alfvén transit time from the substorm onset region to the footprint ionosphere (e.g., Liou et al, 2002). Smith et al (2020) reported that the travel time from the spacecraft to the ground is about 1−2 min for ULF waves in the near-Earth magnetotail. But outside the substorm onset region, the beginning magnetic elevation is smaller than that within the substorm onset region shown in Figure 4g, θ ~ 45°a nd Figure 5g, θ ~ 30°, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The second step is to perform a wavelet analysis on s and compute the significance level. Wavelet analysis have been used in the space sciences for many years to study magnetic phenomena for example, (Lui & Najmi, 1997; Nose et al., 1998; Ochadlick et al., 1993; Smith et al., 2020). The continuous wavelet transform with a sixth order Morlet wavelet is used to determine times and frequency of magnetic activity.…”
Section: Magnetometer Datamentioning
confidence: 99%
“…The growth phase lasts of the order of an hour, during which time the IMF configuration must be conducive to reconnection at the dayside magnetopause (Li et al., 2013). The explosive expansion phase the lasts for around 15–30 min (Forsyth et al., 2015), starting with rapid increases in auroral brightness (Voronkov et al., 2003) and enhanced ultra‐low frequency (ULF) wave activity (Rae et al., 2012; Smith, Rae, Forsyth, Watt, & Murphy, 2020; Smith, Rae, Forsyth, Watt, Murphy, & Mann, 2020). In the magnetosphere, magnetotail currents are diverted into the ionosphere through field aligned currents (see reviews by Kepko et al., 2015; Milan et al., 2017), enhancing the high latitude auroral electrojets and resulting in sharp deflections of the ground magnetic field (Akasofu & Chapman, 1961; Davis & Sugiura, 1966; Forsyth et al., 2018; McPherron et al., 1973; Mann et al., 2008).…”
Section: Introductionmentioning
confidence: 99%